(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Synthesis and crystal structure of 3-3-diamino-N-methyldipropylammonuim hexachlorobismuthate (III) are reported. The compound crystallizes in the triclinic system with space group P1. The unit cell dimensions are: a = 7.5580(5), b =7.8710(6), c = 8.3709(7)… with Z=1. The crystal is built up of separated [BiCl6]3- octahedral anions and 3-3-diamino-N- methyldipropylammonium cations. The organic layers are arranged in sandwich between the anionic ones. The crystal packing is governed by means of the ionic N“HCl hydrogen bonds, forming a three dimensional network.